2017
DOI: 10.1093/cvr/cvx204
|View full text |Cite
|
Sign up to set email alerts
|

Both cardiomyocyte and endothelial cell Nox4 mediate protection against hemodynamic overload-induced remodelling

Abstract: AimsNADPH oxidase-4 (Nox4) is an important reactive oxygen species (ROS) source that is upregulated in the haemodynamically overloaded heart. Our previous studies using global Nox4 knockout (Nox4KO) mice demonstrated a protective role of Nox4 during chronic abdominal aortic banding, involving a paracrine enhancement of myocardial capillary density. However, other authors who studied cardiac-specific Nox4KO mice reported detrimental effects of Nox4 in response to transverse aortic constriction (TAC). It has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 25 publications
3
46
1
Order By: Relevance
“…We showed that the Nox4 expression in the heart of diabetic rats was upregulated while SPR treatment decreased the expression. Interestingly, a recent study showed that Nox4, expressed in both cardiomyocyte and endothelial cells, mediated the protection against hemodynamic overload-induced cardiac remodeling [ 63 ]. The discrepancy between this research and ours may be due to different rodent models.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that the Nox4 expression in the heart of diabetic rats was upregulated while SPR treatment decreased the expression. Interestingly, a recent study showed that Nox4, expressed in both cardiomyocyte and endothelial cells, mediated the protection against hemodynamic overload-induced cardiac remodeling [ 63 ]. The discrepancy between this research and ours may be due to different rodent models.…”
Section: Discussionmentioning
confidence: 99%
“…Nox4 is highly expressed in the kidney and in osteoclasts, fibroblasts, cardiomyocytes, endothelial and vascular smooth muscle cells (Yang et al, 2018;Zhang et al, 2018). It is also abundant in tumour cells and has been considered an oncoprotein (Graham et al, 2010).…”
Section: A Primer On Nox Isoformsmentioning
confidence: 99%
“…Elevated activity of catalase (Figure 8 B) is especially interesting, since cardiac-specific overexpression of catalase has been shown to abolish oxidative stress and prevent the progression to overt HF in an alternative Gαq-overexpressing transgenic mouse model ( 70 ). On the other hand, Nox4-derived hydrogen peroxide both in cardiomyocytes and endothelial cells was shown to mediate protection against pressure overload cardiac remodeling ( 71 ). Our analysis showed that increased activity of CAT was associated with elevated activity of GPx, which overexpression in mice was previously shown to prevent left ventricular failure after myocardial infarction ( 72 ).…”
Section: Discussionmentioning
confidence: 99%